Bauxite residue issues: III. Alkalinity and associated chemistry - Gräfe, M.; Power, G.; Klauber, Craig (Elsevier, 2011)
A detailed understanding of the complex buffering and neutralization chemistry of bauxite residue remains the key to improved management, both in terms of reduced environmental impact for current storage practices, legacy costs and for the utilization of the material as an industrial by-product for other applications. In spite of 120 years of continuous industrial production, the nature of residue and the chemistry of remediation is still poorly understood. This review brings together what is known of residue behavior and outlines the existing knowledge gaps in our understanding. It examines those aspects of the Bayer process that relate to the creation of the alkalinity in residue and discusses in detail the complex chemical reactions that govern the neutralization behavior. pH is the "master variable" in the chemistry of residue and is strongly buffered by the presence of multiple alkaline solids. The pH in untreated residue liquor (washer overflow) ranges over 9.2-12.8 with an average value of 11.3 ± 1.0. This high alkalinity is the primary reason for residue classification as a hazardous material, and in conjunction with the sodic content the primary reason that residue will not support plant life. The pH is highly buffered by the presence of alkaline solids (various hydroxides, carbonates, aluminates and aluminosilicates) that are formed by the action of caustic soda on bauxite in the Bayer process refinery. The presence of such Bayer process characteristic solids causes the acid neutralization behavior of residues to be highly complex and makes impractical the removal of alkalinity by simply washing with water. This chemistry also impacts physical properties e.g. bulk density, sedimentation rates and compaction, hydraulic conductivity, drying rates and dusting behavior, and physical strength after drying. Understanding how surface charge develops, distributes and abates in the residue mineral assemblage as a function of acid input will be paramount to understanding neutralization reactions overall, to successfully model them and eventually to implement the most effective neutralization measures that create conditions at the surface conducive to reduced environmental impact, e.g. to enable plant growth. Once this is understood a model can be constructed for the neutralization behavior of bauxite residue based on the underlying mineralogy and its relationship to overall surface charge. This is the third in a series of four reviews examining bauxite residue issues in detail. © 2011 Elsevier B.V. All rights reserved.